2(x-2)+x=35

Simple and best practice solution for 2(x-2)+x=35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-2)+x=35 equation:


Simplifying
2(x + -2) + x = 35

Reorder the terms:
2(-2 + x) + x = 35
(-2 * 2 + x * 2) + x = 35
(-4 + 2x) + x = 35

Combine like terms: 2x + x = 3x
-4 + 3x = 35

Solving
-4 + 3x = 35

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 3x = 35 + 4

Combine like terms: -4 + 4 = 0
0 + 3x = 35 + 4
3x = 35 + 4

Combine like terms: 35 + 4 = 39
3x = 39

Divide each side by '3'.
x = 13

Simplifying
x = 13

See similar equations:

| 18.36=2.7v | | 7s-35=45 | | (-2z^2-14)-(-12z^2)= | | 108+n=15.72 | | 55+9s=255 | | 4y+7y=12y | | 12(y-11)=5(x-7) | | 5x-7=2(x-1) | | w-16.7=8.24 | | 5x-2x+6x=3x+12 | | 3a^2b-2ab^2=0 | | X+4x+2=13+5x+2 | | -86+4k=102 | | 3a^2-17a+20= | | 60-2x+8x=4x+100 | | 27=3(1-4m)-8(8-7m) | | (2c-6)3-3c=27 | | 4x+27=3y | | 14=-3(-5+6p)+3(1+6p) | | 4(x-3)=-5(6-2x) | | x-4-6+13=x+3 | | 75=5a | | -4d-2(3+d)=-14 | | X=3+4c | | 4x=20-x | | 2n-1=3n | | 4*(3*x-2)-(8*x+6)=6*(2*x-1) | | -x+8=17 | | 2n-1=3n+7 | | 4x-6=8x+8 | | 3x+4yi=4y+15 | | 10.00+2.00=6 |

Equations solver categories